Use of the ECG-Controlled Six-Minute Walk Test to Assess Exercise Capacity: a Comparative Cohort Study - Irina E. Mishina; Olga V. Lebedeva; Elena V. Berezina; Ksenia A. Blinova; Svetlana A. Rachkova; Tatyana V. Pshenichnikova; Yulia V. Chistyakova; Dmitry S. Bykov; Mariam A. Arzumanyan; Soslan N. Gabaraev (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2024)
INTRODUCTION. In clinical practice, stress tests are carried out to draw up an individual patient rehabilitation plan, assess tolerance and optimize the load, and evaluate its clinical effectiveness. The Six-minute walk test (6MWT), in the presence of contraindications to the bicycle ergometer test or the impossibility of performing it, is a tool for assessing the response of the cardiovascular and respiratory systems to the load being performed. There is no description in the literature of the relationship between the distance traveled during 6MWT and the peak metabolic equivalent (MET) assessed during the bicycle ergometer test. AIM. Study the relationship between 6MWT indicators and the results of bicycle ergometer test in patients who have suffered a myocardial infarction. MATERIALS AND METHODS. During the examination, 56 patients underwent a symptom limited bicycle ergometer test and 6MWT, the peak MET and the distance traveled during 6MWT, as well as changes in the ECG during both tests were assessed. RESULTS AND DISCUSSION. The average values of maximum heart rate during the bicycle ergometer test and ECG-controlled 6MWT did not differ significantly. The distance in meters during 6MWT and the power of the exercise performed during bicycle ergometer test in MET have a significant relationship, which indicates the comparability of the data from these tests as a criterion of exercise tolerance. CONCLUSION. The use of 6MWT and bicycle ergometer test allows us to assess various aspects of cardiorespiratory function and physical fitness in patients undergoing a cardiac rehabilitation program. Further study of the possibility of using ECG-controlled 6MWT in the early stages of rehabilitation is necessary to create the most effective and safe physical training for patients who have suffered a myocardial infarction.